2022
DOI: 10.3390/ijms23073736
|View full text |Cite
|
Sign up to set email alerts
|

Role and Regulation of Pif1 Family Helicases at the Replication Fork

Abstract: Pif1 helicases are a multifunctional family of DNA helicases that are important for many aspects of genomic stability in the nucleus and mitochondria. Pif1 helicases are conserved from bacteria to humans. Pif1 helicases play multiple roles at the replication fork, including promoting replication through many barriers such as G-quadruplex DNA, the rDNA replication fork barrier, tRNA genes, and R-loops. Pif1 helicases also regulate telomerase and promote replication termination, Okazaki fragment maturation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 182 publications
(325 reference statements)
0
3
0
Order By: Relevance
“…When dia2Δ cells progress through S-phase, old CMG complexes from the previous cell cycle are removed by an unknown pathway. One candidate factor for such a pathway is the Rrm3 DNA helicase, which together with its paralogue Pif1 is known to help replication forks pass a range of roadblocks on chromatin (Bochman et al , 2010; Malone et al , 2022; Muellner & Schmidt, 2020), such as tightly bound protein-DNA complexes including Mcm2-7 double hexamers (Hill et al , 2020) or stable complexes at tRNA promoters or telomeres (Ivessa et al , 2003; Ivessa et al , 2002), or stable DNA structures such as G-quadruplexes (Kumar et al , 2021; Paeschke et al , 2011; Ribeyre et al , 2009; Williams et al , 2023). Previous work showed that both Rrm3 and Pif1 are important for the viability of dia2Δ cells (Blake et al ., 2006; Morohashi et al ., 2009), and we found that dia2Δ cells lacking both Rrm3 and Pif1 are inviable (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…When dia2Δ cells progress through S-phase, old CMG complexes from the previous cell cycle are removed by an unknown pathway. One candidate factor for such a pathway is the Rrm3 DNA helicase, which together with its paralogue Pif1 is known to help replication forks pass a range of roadblocks on chromatin (Bochman et al , 2010; Malone et al , 2022; Muellner & Schmidt, 2020), such as tightly bound protein-DNA complexes including Mcm2-7 double hexamers (Hill et al , 2020) or stable complexes at tRNA promoters or telomeres (Ivessa et al , 2003; Ivessa et al , 2002), or stable DNA structures such as G-quadruplexes (Kumar et al , 2021; Paeschke et al , 2011; Ribeyre et al , 2009; Williams et al , 2023). Previous work showed that both Rrm3 and Pif1 are important for the viability of dia2Δ cells (Blake et al ., 2006; Morohashi et al ., 2009), and we found that dia2Δ cells lacking both Rrm3 and Pif1 are inviable (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…RAD51 is a hallmark protein of homologous recombination [56,57]. BIR is a form of homologous recombination that involves the repair of single-ended DNA DSBs on folded replication forks [9]. PIF1 readily localizes to replication-associated fragile sites, inducing BIR [25].…”
Section: Discussionmentioning
confidence: 99%
“…PIF1 helicase (5 →3 DNA helicase), a member of the helicase superfamily 1, translocates along singlestranded DNA and unwinds double-stranded DNA in the 5 →3 direction [8]. PIF1 helicases localize to and facilitate the advancement of replication forks [9]. Additionally, PIF1 facilitates Okazaki fragment synthesis [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pif1 helicase has been identified in S. cerevisiae as a protein with multiple functions. Pif1 is involved in DNA repair and is necessary for the maintenance of mitochondrial and nuclear genomes integrity, in the regulation of telomerase activity and in the replication fork progression (reviewed in [ 3 , 4 , 5 , 6 ]). Many functions of Pif1 could be explained by its specific activity towards G-quadruplexes (G4), a particularly stable structure of NA which can be adopted by Guanine-rich sequences [ 7 ].…”
Section: Introductionmentioning
confidence: 99%